Leishmania donovani populations in Eastern Sudan: temporal structuring and a link between human and canine transmission - Rania Baleela; Martin S Llewellyn; Sinead Fitzpatrick; Katrin Kuhls; Gabriele Schönian; Michael A Miles; Isabel L Mauricio (Parasites & Vectors, 2014)
Abstract Background Visceral leishmaniasis (VL), caused by the members of the Leishmania donovani complex, has been responsible for devastating VL epidemics in the Sudan. Multilocus microsatellite and sequence typing studies can provide valuable insights into the molecular epidemiology of leishmaniasis, when applied at local scales. Here we present population genetic data for a large panel of strains and clones collected in endemic Sudan between 1993 and 2001. Methods Genetic diversity was evaluated at fourteen microsatellite markers and eleven nuclear sequence loci across 124 strains and clones. Results Microsatellite data defined six genetic subpopulations with which the nuclear sequence data were broadly congruent. Pairwise estimates of FST (microsatellite) and KST (sequence) indicated small but significant shifts among the allelic repertoires of circulating strains year on year. Furthermore, we noted the co-occurrence of human and canine L. donovani strains in three of the six clusters defined. Finally, we identified widespread deficit in heterozygosity in all four years tested but strong deviation from inter-locus linkage equilibrium in two years. Conclusions Significant genetic diversity is present among L. donovani in Sudan, and minor population structuring between years is characteristic of entrenched, endemic disease transmission. Seasonality in vector abundance and transmission may, to an extent, explain the shallow temporal clines in allelic frequency that we observed. Genetically similar canine and human strains highlight the role of dogs as important local reservoirs of visceral leishmaniasis.